PERBANDINGAN TEKANAN DARAH ANTARA PEROKOK DAN BUKAN PEROKOK TERHADAP PENDERITA HIPERTENSI DI DESA CIMPU - Purba, Sulastri; Haedir, Haedir; Iskandar, Iskandar; Tandiallo, Devianti; Muzfah, Wardah; Abdal, Fitriani; Rijal, Rijal (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
The smoking behavior of Indonesian people has an impact on health, namely suffering from hypertension. Nicotine in cigarettes can increase blood pressure, while carbon monoxide can reduce the amount of oxygen carried in the blood. This study aims to analyze whether there is a comparison of blood pressure between smokers and non-smokers with hypertension sufferers in Cimpu Village, Suli District, Luwu Regency in 2023. The type of research used is a comparative study with a cross-sectional design. As for the comparison of the blood pressure of smokers and non-smokers in hypertension sufferers in Cimpu Village, Suli District, Luwu Regency in 2023 with a systolic p value of 0.000 <0.025, the result is that there is a significant difference between the blood pressure of smokers and non-smokers. It is hoped that hypertensive patients can stop smoking, so that they can improve their health status and reduce the incidence of hypertension.